TERRORISM AS A FORM OF ORGANIZED CRIME - Nacev, Aleksandar; Kostevska, Dragana (International Scientific Journal Vision, 2022)
Terrorism is not a 21st century phenomenon and has its roots in early resistance and political movements. It is important to mention that for terrorism there is no universally agreed definition which makes it a difficult object to quantify. Its effects are the unlawful use of violence and intimidation, especially against civilians, in the pursuit of political aims. In other words it is represented by danger, helplessness and sadness. Terrorism represents illegal use of force or violence against people or property, in order to infuse fear and panic and to achieve a specific goal. This scientific paper, explains conjunction between organized crime and terrorism. With their practical actions, for easily achieving their goals, these two types of serious crimes use methods from other types of crime. When their interests coincide, they can connect to each other, to cross operate. The unsolved question is whether terrorism is in function of organized crime or is organized crime functioning for the terrorism. Terrorism is characterized by: organizing, training, equipping, brutality and inhumanity. It is present in all systems of human life. Until now, no society was able to protect completely itself from terrorist attacks. Today's concept of organized crime is heterogeneous and contradictory when we take into account the entire range of pertinent statements in the criminal-policy debate. Having in mind that for these two phenomena there is no universal and comprehensive definition we should not be surprised with the fact that there are different opinions and views on the next thought: whether terrorism is a form of organized crime, or are they two separate types and does organized crime support and encourage terrorism.